2020
DOI: 10.1038/s41598-020-70936-9
|View full text |Cite
|
Sign up to set email alerts
|

Paretic knee extensor strength, gait velocity, and fat mass are major determinants of peak aerobic capacity in subacute stroke: observational cohort study

Abstract: the purpose of this study is to investigate major determinants of peak aerobic capacity in subacute stroke patients among body composition, balance function, walking capacity, and lower limb muscular strength. this was a retrospective observational cohort study. eighty-three subacute stroke patients were enrolled and their medical records were retrospectively reviewed in the study (47 males; mean age: 62.95 ± 13.9 years). Gait capacity was assessed by gait velocity (10 m walk velocity:10MWV) and gait endurance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…[ 27 ] Similarly, another study reported that knee extensor strength is closely related to gait endurance of stroke survivors. [ 13 ] Between Group A and Group B, there were statistically significant differences of BBS, mRS, and MBI. This indicates that paretic knee extensor power has an influence on the standing balance and physical functions of stroke survivors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 27 ] Similarly, another study reported that knee extensor strength is closely related to gait endurance of stroke survivors. [ 13 ] Between Group A and Group B, there were statistically significant differences of BBS, mRS, and MBI. This indicates that paretic knee extensor power has an influence on the standing balance and physical functions of stroke survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have noted that quadriceps is the main muscle responsible for ambulatory capacity, functional mobility, and would be a predictor of walking performance in stroke patients. [ 12 , 13 ] The earlier studies reported that a minimum of grade 3 of knee extensor strength is required for community ambulation. [ 22 , 23 ] Accordingly, we divided the patients into 2 groups based on the grade 3 of the paretic knee extensor power, and compared several parameters between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations